Estudo de propriedades estruturais de nanomembranas semicondutoras - Lucas Atila Bernardes Marcal (2015)
This work is composed of three independent results in which X-ray diffraction measurements, finite element modeling and photoluminescence are used to determine structural and optical properties of semiconductor nanostructures. In the first part of this thesis, properties of InAs quantum dots in a GaAs (001) matrix with AlGaAs barriers were studied. Once released from their growth support (wafer) these layers become nanometer-thick membranes (or nanomembranes), in which the presence of surfaces in the vicinity of the nanostructures can induce changes in their elastic strain status, as well as on their optical properties. X-ray diffraction measurements allowed the verification of the crystalline quality of the films, while finite element analysis and photoluminescence measurements explored the effects of elastic relaxation and quantum confinement in the nanostructures. In the second part of this thesis a spatially resolved x-ray diffraction technique was used to map the sample with nanometer resolution. This method allowed the reconstruction of three-dimensional reciprocal space maps, which were used to determine the strain transfer from InAs nanostructures to a Si (001) nanomembrane. Finite element method was again used, providing a quantitative interpretation of the experimental data. In the third part of this thesis finite element simulations were used to directly reproduce x-ray diffraction data, allowing the comparison and analysis of results in reciprocal space. We used x-ray diffraction measurements on samples containing InGaAs rings on GaAs (001) as experimental case. The main goal was to determine the InGaAs/GaAs interfacial strain, as well as the possible stacking conditions of a double quantum ring layer.